Model Pembelajaran Inovatif Ma’had Al-Jamiah UIN Sunan Ampel Surabaya; Upaya Pengembangan Karakter dan Pengalaman Belajar Holistik Mahasantri - Rifa'i, Bahtiyar (EL-BANAT: Jurnal Pemikiran dan Pendidikan Islam, 2023)
This qualitative descriptive research aims to provide an analysis of the learning models used by Ma'had al-Jami'ah UIN Sunan Ampel Surabaya in forming the character of mahasantri. The research collection techniques used were interviews, observation and documentation with the aim of exploring various models used in building mahasantri character. The results of the research show that there are several approaches used in forming the character of mahasantri in Ma'had al-Jami'ah. These models include good habits towards students, role modeling, discipline development, as well as through participatory learning. These models reflect Ma'had al-Jami'ah's innovative efforts in creating a conducive educational environment and providing a holistic learning experience for students.